EVALUASI PELAKSANAAN PELAYANAN KEFARMASIAN DI APOTEK WILAYAH KOTA TEGAL TAHUN 2018 (BERDASARKAN PERMENKES NO 35. TAHUN 2014) - Sari Prabandari; Anggy Rima Putri (Pusat Penelitian dan Pengabdian Masyarakat Politeknik Harapan Bersama, 2019)
The government issued Minister of Health Regulation No. 35 of 2014 concerning Pharmacy Standards at the Pharmacy to serve as guidelines for pharmacist practice in carrying out professional duties to protect the community from Services. The purpose of this study is to find out the evaluation of the standard implementation of pharmaceutical services at the Tegal City Regional Pharmacy in 2018. This research is a descriptive quantitative analysis research. The source of the primary research data and tools in this study is a questionnaire sheet. Research Results from the Management Aspects of Pharmaceutical Preparations and Pharmacy Health Supplies in the City of Tegal Has carried out the management of Pharmaceutical Preparations with Good Category, as well as the Aspects of Pharmacy Resource Management in terms of the presence of Pharmacists and Medical Personnel, but there is less to the presence or absence of pharmacists at the Pharmacy. The aspects of facilities and infrastructure in providing a closed space for counseling can only be said to be sufficient. Aspects of Clinical Pharmacy Services are said to be lacking for monitoring drug therapy, monitoring drug side effects, and home care1. From the aspect of evaluation of service quality, recording medication records is said to be lacking. Whereas the quality of clinical services is also said to be good for attention to allergies, pharmaceutical examination of drugs, and examination of drug availability, but lack of attention to dual medications and contraindications. As well as in the dimension of waiting time, drug service is said to be sufficient.Keywords: Pharmacy, Pharmacy Service, Permenkes No. 35 of 2014